Testing a Self-Compassion Intervention Among Job Seekers: Self-Compassion Beneficially Impacts Affect Through Reduced Self-Criticism - Kreemers, Loes M.; van Hooft, Edwin A. J.; van Vianen, Annelies E. M.; Sisouw de Zilwa, Sophie C. M. (Frontiers in Psychology, 2020)
Job search is associated with various obstacles and difficulties that can elicit negative emotions and undermine positive emotions. Having self-compassion may benefit job seekers’ well-being by stimulating more balanced emotional responses to negative job search experiences. In an intervention study we examined whether state self-compassion can be increased among job seekers through writing exercises in which job seekers are instructed to reflect with self-compassion on their negative job search experiences. We further examined whether the self-compassion intervention benefited job seekers’ affective responses, through reducing self-criticism. We designed a between-participants field experiment with two conditions (i.e., self-compassion vs. control) and three measurement times 1 week apart: a baseline questionnaire, the intervention with a second questionnaire, and a follow-up questionnaire (N = 180). Results show that the self-compassion writing exercise increased job seekers’ state self-compassion, which in turn related to their affective responses to job search. Specifically, their negative deactivating affect (e.g., sadness) was lower and their positive deactivating affect (e.g., calmness) was higher immediately after the self-compassion writing exercise than after reflecting freely (i.e., the control condition). The effects on job seekers’ affect were partially mediated by reduced self-criticism.